Small but active – pool size does not matter for carbon incorporation in below‐ground food webs. (6th August 2015) - Pausch, Johanna; Kramer, Susanne; Scharroba, Anika; Scheunemann, Nicole; Butenschoen, Olaf; Kandeler, Ellen; Marhan, Sven; Riederer, Michael; Scheu, Stefan; Kuzyakov, Yakov; Ruess, Liliane
Summary: The complexity of soil food webs and the cryptic habitat hamper the analyses of pools, fluxes and turnover rates of carbon (C) in organisms and the insight into their interactions. Stable isotope analysis has been increasingly used to disentangle soil food web structure, yet it has not been applied to quantitatively characterize C dynamics at the level of the entire soil food web. The present study employed 13 CO2 pulse labelling to investigate the incorporation of maize root‐derived C into major soil compartments and food web players in an arable field for 25 days. Bulk tissue and compound‐specific (lipids) C isotope ratios were used to quantify pool sizes and 13 C incorporation in bacteria and fungi as primary decomposers, nematodes as key drivers of the microfood web and decomposers and predators among the meso‐ and macrofauna. About 20% of the C assimilated by maize was transferred to below‐ground pools. 13 C was predominantly incorporated into rhizosphere micro‐organisms rather than in those of the bulk soil. 13 C in phospholipid fatty acid biomarkers revealed that root‐derived C was incorporated into the soil food web mainly via saprotrophic fungi rather than via bacteria. Only small amounts of 13 C were transferred to higher trophic levels, predominantly into fungal‐feeding nematodes and macrofauna decomposers. Most importantly, C pool size and 13 C incorporation did not match closely. Although the fungal C stock was less than half that of bacteria, C transfers from fungi into higher trophic levels of the fungal energy pathway, that is fungal‐feeding nematodes and meso‐ and macrofauna decomposers, by far exceed that of bacterial C. This challenges previous views on the dominance of bacteria in root C dynamics and suggests saprotrophic fungi to function as major agents channelling recent photoassimilates into the soil food web. Abstract : Lay Summary